(untitled) (Research, Society and Development, 2022)
Covid-19 had an impact on education, so this research aimed to understand how students from Ceará experienced home studies, through or without Emergency Remote Education (ERE). The case study, with a qualitative and quantitative approach, was carried out with questionnaires, answered by 1317 students. The calculation of the average ranking and content analysis were used in the data. Students consider learning below average and expressed interest in the partial use of digital interfaces. Anxiety and dispersion were associated with learning difficulties and the return to face-to-face activities still causes fears. It is concluded that the ERE, despite the controversies, contributed to the learning in the pandemic.